Melissopalynological, Physicochemical, Antimicrobial and Microbiological Attributes of Commercial Honeys from North West Nigeria - Mazai, Husaina M.; Ibrahim, Sani; Muhammad, Aliyu; Abubakar, Abdulmumin Z. (Current Nutrition & Food Science, 2020)
Background: Honey is used for nutritional, medicinal and industrial purposes and maintenance of the requisite quality is of great importance. Objective: This study distinctively aimed to portray twelve randomly selected profitable honeys accessible in the North West Nigerian market with regards to floral nectar origin, physicochemical factors, antimicrobial activity and microbial safety evaluations. Methods: Twelve (12) samples of honey sourced from diverse places in the Northwest of Nigeria were analyzed for their pollen spectra, physicochemical parameters, antimicrobial activity and microbiological safety. Results: Dominant pollen types from the analysis were Borassus (72%), Piptadenia africana (39%), Lophira (91%) and Combretaceae (91%) for Sokoto, Jigawa, Kaduna and Katsina States honey samples, respectively. The physicochemical analysis of the samples revealed that pH was in range from 3.32 to 4.25, moisture content varied from 16.37% to 18.70%, ash content 0.23% to 0.93% and free acidity 6.83meq/Kg to 32.00meq/kg, electrical conductivity ranged from 0.13mS/cm to 1.40mS/cm, reducing sugars was 42.85% to 49.30%, sucrose content was 0.74% to 6.75%, Hydroxymethylfurfural value was 11.0mg/Kg to 80.20mg/Kg, diastase level ranged from 7.23 to 43.5 and Proline content ranged from 104.67mg/Kg to 666.67mg/Kg. The antimicrobial evaluation revealed significant zone of inhibition to E. coli, ranging from 19-38 mm at concentrations (12.5-100mg/mL) tested as compared to all other test organisms. Conclusion: The fallouts of microbiological investigation of the samples revealed mould and bacteria, with counts less than 102CFU/g. The findings showed that the attributes of the tested honey samples maintained criteria of international standards.
Keywords: microbiology